2010
DOI: 10.3164/jcbn.10-62
|View full text |Cite
|
Sign up to set email alerts
|

Soybean-Derived Phosphatidylserine Improves Memory Function of the Elderly Japanese Subjects with Memory Complaints

Abstract: Soybean-derived phosphatidylserine (Soy-PS) is a phosphatidylserine made from soybean lecithin by enzymatic reaction with L-serine. A double-blind, randomized controlled study was conducted to investigate the effects of Soy-PS on the cognitive functions of the elderly Japanese subjects with memory complaints. Seventy-eight elderly people with mild cognitive impairment (50–69 years old) were randomly allocated to take Soy-PS (100 mg, 300 mg/day) or placebo for 6 months. As a result, there was no difference in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 28 publications
2
55
0
2
Order By: Relevance
“…Kato-Kataoka et al [43] conducted a similar double-blind, randomized study on 78 subjects (50 -69 years old) to determine if 100 -300 mg oral PS per day versus placebo affected memory scores. They found that PS significantly improved behavioral memory functions, especially short-term memory and cognitive function in low-scoring (delayed word recall) participants (p < 0.01) [43].…”
Section: Other Clinical Uses Of Membrane Lipid Replacementmentioning
confidence: 99%
“…Kato-Kataoka et al [43] conducted a similar double-blind, randomized study on 78 subjects (50 -69 years old) to determine if 100 -300 mg oral PS per day versus placebo affected memory scores. They found that PS significantly improved behavioral memory functions, especially short-term memory and cognitive function in low-scoring (delayed word recall) participants (p < 0.01) [43].…”
Section: Other Clinical Uses Of Membrane Lipid Replacementmentioning
confidence: 99%
“…Da ly viai buvo su skirs ty ti á tris gru pes, ku riø kiek vie na kas dien var to jo pla ce bà ar ba 100/300 mg ið so jø pu pe liø ið gau tà fos fa ti dilse ri nà. Pa ly gi nus vi sø ti ria mø jø gru piø kog ni ty vi niø tes tø re zul ta tus po 9 ty ri mø më ne siø, reikð min gø skir tu mø tarp gru piø ne ras ta [47].…”
Section: Maisto Papildaiunclassified
“…However, many reports have shown cognitive improvement. The most recent study of PS was a double-blind, placebo-controlled trial in elderly Japanese patients with mild memory impairment [7]. The participants were prescribed Soy-PS or placebo in dosages of 100 mg or 300 mg per day for 6 months.…”
Section: Treatment Of Dementiamentioning
confidence: 99%